Soil Physical Quality and Relationship to Changes in Termite Community in Northwestern Colombian Amazon - Duran-Bautista, Ervin Humprey; Muñoz Chilatra, Yolima; Galindo, Juan Diego; Ortiz, Tania Alexandra; Bermúdez, María Fernanda (Frontiers in Ecology and Evolution, 2020)
Conversion from Amazon forest to low-management pasture or agriculture causes not only degradation of aboveground vegetation but also negative changes in soil properties and ecosystem services. This study aimed to evaluate the impact of physical soil degradation on termite community changes in three contrasting land uses (natural regeneration, rubber plantations, and silvopastoral systems). Soil physical quality was assessed through a set of physical variables such as bulk density, porosity, soil macro-aggregation state, Visual Evaluation of Soil Structure (VESS) and penetration resistance, and physical soil, which were summarized in an overall synthetic indicator of physical quality. Besides, transects of 20 x 2 m were established in each land use, each transect was divided into four sections of 5 m to search and collect termites during one hour in each section, likewise, termites were collected from blocks of soil 25 x 25 x 10 cm (length, width, and depth, respectively) adapted from Tropical soil biology and fertility (TSBF ) method. In total 60 transects were evaluated, 20 in each land use. A total of 41 species were collected across the three land uses evaluated, natural regeneration presented 60% of the collected species (25 species), silvopastoral systems 53% (22 species) and rubber plantations 39% (16 species). Additionally, composition species from the silvopastoral, agroforestry systems and natural regeneration was different, and a close association between these last land uses was observed. Soil physical characteristics showed significant variations between land uses, rubber plantations presented lowest values of soil physical quality, meanwhile, the natural regeneration showed high soil physical quality. These changes affected termite community and lead to changes in its composition with disproportionate loss of some species, however, there are some that can acclimated well to the decline in soil physical quality